2014
DOI: 10.1111/jcpt.12137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating sustained quality improvements: long-term effectiveness of a physician-focused intervention to reduce potentially inappropriate medication prescribing in an older population

Abstract: The significant reduction in the odds of PIP exposure achieved during the intervention was sustained after its discontinuation. Because the intervention showed success across the spectrum of patients and providers, it shows promise for generalizability to other healthcare settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
2
18
0
1
Order By: Relevance
“…Our findings substantiate previous findings that have demonstrated that interventions lasting for a limited time period (e.g. educational and multifaceted interventions) can have a long-lasting carry-over effect on improving PIP [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings substantiate previous findings that have demonstrated that interventions lasting for a limited time period (e.g. educational and multifaceted interventions) can have a long-lasting carry-over effect on improving PIP [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…The 2007 Maio criteria list was assessed in a prospective, proof‐of‐concept, quality improvement initiative in the Local Health Authority (LHA) of Parma, one of the 11 regional LHAs. This initiative targeted all Parma LHA general practitioners (GPs) with an aim to ameliorate physician‐prescribing behaviour and significantly reduce PIM exposure in older patients . Given the positive results of the intervention in the Parma LHA, the RER has granted the expansion of the quality intervention to all RER GPs in the 11 regional LHAs.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…These criteria classify medications based upon the estimated risk of clinical harm vs. clinical benefit , with PIMs defined by an estimate of net harm when the medication is used for the population under consideration. These criteria can be used as clinical guidelines to evaluate the prevalence of PIM exposure, develop interventions and evaluate postintervention trends . Ultimately, the main purpose of these criteria is to improve clinical outcomes; however, the links between PIM exposure and prominent health outcomes of interest to patients and health system stakeholders remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging a large, comprehensive, longitudinal database in the Emilia‐Romagna region of Italy, we sought to evaluate the relationship between PIM exposure and hospitalization. Specifically, our aim was to determine whether current PIM exposure increases the rate of hospitalization, while defining PIM exposure using an Italian‐modified version of the Beers criteria – namely, the Maio criteria . Additionally, we estimated the rate of hospitalization during exposure to each individual PIM.…”
Section: Introductionmentioning
confidence: 99%